Corosolic acid analogue, a natural triterpenoid saponin, induces apoptosis on human hepatocarcinoma cells through mitochondrial pathway in vitro. (2nd August 2016) - Qu, Liping; Zhang, Huiqing; Yang, Yanlong; Yang, Geliang; Xin, Hailiang; Ling, Changquan
Abstract: Context 2a, -3a, -24-Trihydroxyurs-12-en-28-oic acid (TEO, a corosolic acid analogue) is a triterpenoid saponin isolated from Actinidia valvata Dunn (Actinidiaceae), a well-known traditional Chinese medicine. Objective This study investigated the anti-proliferation and inducing apoptosis effects of TEO in three human hepatocellular carcinoma (HCC) cell lines. Materials and methods Cytotoxic activity of TEO was determined by the MTT assay at various concentrations from 2.5 to 40 μg/mL in BEL-7402, BEL-7404 and SMMC-7721 cell lines. Cell morphology was assessed by acridine orange/ethidium bromide and 4′-6-diamidino-2-phenylindole dihydrochloride staining and fluorescence microscopy. Cell-cycle distribution and DNA damage were determined by flow cytometry and comet assay. Mitochondrial dysfunction was assessed by JC-1 staining and transmission electron microscopy. Apoptosis changes were explored by Western blot, TNF-α and caspase-3, -8, -9 assays. Results TEO exhibited inhibition effects on BEL-7402, BEL-7404 and SMMC-7721 cells treated for 24 h, the IC50 values were 34.6, 30.8 and 30.5 μg/mL, respectively. TEO (40 μg/mL)-treated three cell lines increased by more than 21% in the G1 phase and presented the morphological change and DNA damage. TEO also declined the mitochondrial membrane potential and altered mitochondrial ultra-structure. Furthermore, caspase-3, caspase-8, caspase-9 and TNF-α were also activated. Mechanism investigation showed that TEO could decrease anti-apoptotic Bcl-2 protein expression, increase proapoptotic Bax and Bid proteins expressions and increase Bax/Bcl-2 ratio. Conclusion Our results demonstrate for the first time that TEO inhibited growth of HCC cell lines and induced G1 phase arrest. Moreover, proapoptotic effects of TEO were mediated through the activation of TNF-α, caspases and mitochondrial pathway.